Determinants of intention to adopt cloud computing among Malaysians - Wong, Hao Juen (2019)
The enhancement of information technology (IT) leading a convenience life for people in Malaysia. The cloud computing also serves as one of it, however, it seems like not much Malaysians are aware and adopt it, hence, this study is conducted with a purpose to understand the determinants that influencing the intention of cloud computing adoption. The determinants are Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Perceived Risk (PR). The theory base is the Technology Acceptance Model (TAM), this study only slightly alters it; quantitative research method is adopted, and Multiple Linear Regression model is the main analysis model for this study. As resulted, the intention to adopt indeed are impacted significantly by the PU and PR, only the PEOU is not. Therefore, it is to be said that the level of difficulty to adopt a particular system is not significance in today, the usefulness and risk serve as the important criteria that influencing the intention.